Machado de assis and reverse criticism - Azevedo, Sílvia Maria [UNESP] (FapUNIFESP (SciELO), 2015)
During the time he collaborated with the cartoon magazine Semana Ilustrada [Illustrated Week] (1860-1876), Machado de Assis, under the pen name of Dr. Semana, was the author of a number of chronicles in which a different kind of criticism, called reverse criticism by Raimundo Magalhães Júnior, emerged. This criticism consisted in flattering texts that were terrible from the literary viewpoint. Based on the theoretical formulations of Beth Brait and Linda Hutcheon regarding irony, the article aims to analyze some examples of this kind of criticism that arises in Semana Ilustrada, in which it is possible to identify the first signs of Machado's unreliable narrator.
Keywords: Irony; Machado de assis; Reverse criticism